Clinical Applications of Otoacoustic Emission: A Review of the Indications in Aminu Kano Teaching Hospital Northern Nigerian - Bello‑Mohammed, Nafisa; Hasheem, Muhd (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: An otoacoustic emission (OAE) is a low-level sound emitted by the cochlea either spontaneously or evoked by an auditory stimulus. Objectives: To determine cochlea status, specifically outer hair cells (OHC), and to determine the indications and utilization of Otoacoustic emission in Aminu Kano Teaching Hospital. Settings and Design: This was a 3 years retrospective analysis in which all patients that had Otoacoustic Emission in Aminu Kano Teaching Hospital from January 1, 2018 to December 31, 2021. Materials and Methods: The records were retrieved and the basic demographic data, indications, and findings were extracted and entered into the Excel spreadsheet. Statistical Analysis Used: Retrospective analysis of the indications of otoacoustic emission testing was done by analyzing the records of 146 patients. The data were extracted and analyzed using SPSS version 22.0 and the result presented in tables. Results: Hearing loss accounted for 37% of OAE testing done (55 patients). Hearing loss from febrile illness accounted for 12.3% (18 patients) and 12% resulted from congenital hearing loss (16 patients). Conclusion: OAEs continue to play an important role in routine audiological assessments with ever-expanding applications. There is, however, marked under-utilization of the investigation. Hopefully, the scope of applications will broaden to include hearing aid fitting and intraoperative monitoring, and using OAE as “acoustic fingerprints” becomes a reality. There is a need for more commitment by the ORL Surgeons.